Respuesta :
Answer:
B. [tex]\frac{b}{2a^{2}c^3}\sqrt[3]{15b}[/tex]
Step-by-step explanation:
Given:
The expression to simplify is given as:
[tex]\sqrt[3]{\frac{75a^7b^4}{40a^{13}c^9}}[/tex]
Use the exponent property [tex]\frac{a^m}{a^n}=a^{m-n}[/tex]
[tex]\frac{a^7}{a^{13}}=a^{7-13}=a^{-6}[/tex]
Use the exponent property [tex](a^m)^n=a^{m\times n}[/tex]
[tex]a^{-6}=a^{-2\times 3}=(a^{-2})^3[/tex]
[tex]b^4=b\times b^3\\c^{9}=(c^3)^3[/tex]
Reducing [tex]\frac{75}{40}[/tex] to simplest form, we get:
[tex]\frac{5\times 5\times 3}{2^3\times 5}=\frac{15}{2^3}[/tex]
Therefore, expression becomes:
[tex]\sqrt[3]{\frac{15(a^{-2})^3\times b\times b^3}{2^3(c^3)^3}}[/tex]
Use the cubic root property:
[tex]\sqrt[3]{x^3} =x[/tex]. Thus, the expression becomes:
[tex]\frac{a^{-2}b}{2c^3}\sqrt[3]{15b}[/tex]
Using the exponent property [tex]a^{-m}=\frac{1}{a^m}[/tex]
[tex]a^{-2}=\frac{1}{a^2}[/tex]
So, the final expression is:
[tex]\frac{b}{2a^{2}c^3}\sqrt[3]{15b}[/tex]
Therefore, the correct option is option B.